Experimentally induced cranial cruciate ligament ruptures with repair of caudal tibial muscle and evaluation of its outcome in dogs - Ünsaldi, Emine; Karabulut, Enis; Sa?liyan, Aydin (Veteriner Fakultesi Dergisi, 2011)
This study examined the repair of experimentally induced cranial cruciate ligament (CrCL) ruptures with caudal tibial muscle (MTC). Clinical, necroscopical, histopathological and magnetic resonance imaging (MRI) evaluation of the dogs were made determine whether this tendon could be used as a new alternative in the repair of CrCL ruptures. The operation was carried out 10 dogs over 15 kg with different breeds, ages and sexes. Under anesthesia, CrCL was excised through lateral parapatellar approach. The medially located insertion of the MTC tendon was carefully cut to free up to the proximal end of the tibia. The tendon remained attached to the tibia with its origin was spined up to its freed end with polyglactin suture material. Then, an intraarticular tunnel in a manner openning to the right medial aspect of the proximal articular facet of the tibia (i.e. toward the insertion of the cruciate ligament to the tibia) was established with 4.5 mm drill. A second tunnel in lateral femoral condylus in the direction of the insertion to the CrCL was established. The tendon prepared before was passed through this tunnels and fixed in place with one or two screws. Each of the dogs was monitored during a year for performing clinical examinations. MRI was taken at the 3rd, 6th and 12th months of the study. Following euthanasia at the 12th month the reconstructed cranial cruciate ligaments of all dogs were histopathologically examined. Clinically all cases were observed to use their extremities normally at the 6th month. MRI demonstrated an impingement in the tunnel of one case, continuous band with low signal density at the intra-articular spaces of the cruciate ligament and the tunnels of the remaining cases and aslo the presence of grafts in the intra-articular spaces as well as the tunels of tibia and femur of all cases. According to these results, it was concluded that the use of caudal tibial muscle tendon can be appropriate for the reconstruction of cranial cruciate ligament rupture in dogs.
Köpeklerde deneysel olarak oluşturulan ön çapraz ba? kopmalarının m. tibialis caudalis kullanılarak sa?altılması ve sonuçlarının de?erlendirilmesi
Keywords: Caudal tibial muscle; Cranial cruciate ligament; Dog; Repair; Ruptur